Shared versus nonshared effects: Parenting and children’s adjustment - Pike, Alison; Kretschmer, Tina (International Journal of Developmental Science, 2009)
Including more than one child per family in research enables the identification of nonshared family effects (resulting in sibling differentiation) as well as shared family effects (resulting in sibling similarity). This paper describes a model used to disentangle shared from nonshared processes in links between parenting and children’s behavior. The sample consisted of 172 families with two children aged four to eight years. Children and parents provided reports of parenting, and parents also reported on the children’s behavior problems. According to mothers, parenting of children within families was largely similar, however the children’s reports (via puppet interviews) indicated substantial differential treatment. In addition, links between parenting and behavior problems were largely nonshared-reinforcing the message from behavioral geneticists that parenting functions on a child-by-child rather than family-by-family basis. That is, rather than serving to make their children similar to one another, these findings support the idea that parent-child interactions lead to unique developmental trajectories for children. © 2009 Vandenhoeck & Ruprecht GmbH & Co.
CRIS-Team Scopus Importer:2025-03-19
Keywords: Nonshared environment; Parenting; Problem behavior; Shared environment; Siblings